PENGARUH ELECTRONIC WORD OF MOUTH TERHADAP KEPUTUSAN MENGINAP BAGI TAMU FIT (FREE INDEPENDENT TRAVELLER) : STUDI KASUS DI HILTON BALI RESORT - I Gusti Ayu Putu Diah Adnyani; Putu Diah Sastri Pitanatri (JURNAL BISNIS HOSPITALITI, 2017)
Electronic word of mouth especially those created in TripAdvisor undianably helped many hotels in building its image. The reason is simply because the written reviews will build a hotel’s image, thus affecting purchase decision of its potential customers. Looking into this phenomenon, by using Hilton Bali Resort as the case study, this research aims to determine the effect of electronic word of mouth for FIT guests in making hotel reservation at Hilton Bali Resort. The data were collected by documentation study and questionnaire. After that, it is being analyzed by using quantitative descriptive analysis techniques, simple regression analysis, Pearson Product Moment correlation analysis, coefficient of determination analysis and T-test. Based on research results, it can be concluded that the existence of electronic word of mouth on Tripadvisor simultaneously have a significant and positive influence in making hotel reservation for FIT guests at Hilton Bali Resort. Therefore, the management of Hilton Bali Resort is expected to maintain a goodbrand image of the hotel, more communicative in interacting with guests in the opinion platforms owned and design a promotional program that can further establish emotional closeness with consumers.